ӘЖИНИЯЗ ШЫҒАРМАЛАРЫ ТИЛИНДЕ СИНОНИМЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Қарлыбаева, Г.Е. (FAN va JAMIYAT, 2016)
The article is devoted to the study of stylistic peculiarities of synonyms in the works of the Karakalpak poet-classic of the XIX_-th century Ajiniyaz. The author also studies the issues of polysemy and the structure of synonyms‘ compenents. On the basis of the analysis of practical material there have been studied the lexical and contextual synonyms.